Cold shoulders and napkins handed: gestures of responsibility - Laurier, Eric; Philo, Chris (Wiley InterScience, 2006)
Cafes are places in the city in which we have come to expect conviviality between the unacquainted. Goffman is perhaps the most famous analyst of relations between strangers in public space, yet his depiction of society's members points towards a misanthropic form of life. Drawing on video footage shot during ethnographic research, this paper analyses gestures made between strangers in cafés and how they produce cafés as cold, receptive or accommodating places. It considers how we might move on from Goffman's work to an understanding of urban life that includes the possibility of more than the impression of conviviality.
Keywords: Human Geography; ethnomethodology